Effect of Forsus-assisted mandibular advancement on the adaptation of craniocervical posture – A retrospective study - Preethi Rajamanickam; Remmiya Mary Varghese; Shreya Kishore (Journal of Orthodontic Science, 2024)
BACKGROUND and OBJECTIVE: Skeletal Class II malocclusion patients frequently exhibit an extended craniocervical position. The study’s objective was to evaluate how the craniocervical posture has changed following skeletal class II correction using the Forsus fatigue-resistant device (FFRD). METHODOLOGY: A retrospective analysis was undertaken using the pre- and post-treatment records of 35 skeletal class II patients who used the FFRD to achieve class II correction. The metrics suggested by Solow and Rocabado were used to evaluate the cranial and cervical positions. Eleven angular parameters were evaluated to determine the relationship between the mandibular ramus and the skull as well as the upper and middle craniocervical positions. To compare the parameters before and after fixed functional therapy, a Wilcoxon signed rank test was used. RESULTS: Significant differences were obtained in the parameters SNA, SNB, and ANB post-FFRD. Significant differences were also noted in NL/OPT, NSL/OPT, FH/CVT, FH/OPT, NSL/CVT, NL/CVT, ML/CVT, FH/RL, and oropharynx position. CONCLUSIONS: The upper and middle craniocervical posture altered significantly with the FFRD. Skeletal class II correction obtained with FFRD delivered the patients a more erect craniocervical posture.